The effective executive - Drucker, Peter F. (London : Heinemann, 1967)
This book presents the authors finding. The most important thing to report is that he had found that effectiveness can be learned - but also that it must be learned.
Includes bibliographical references and index
hza 24/09/2018
Loans
Keywords: Industrial management; Decision making